Impact of crusader castles upon European western castles in the Middle Ages - Hampe, Jordan (My University, 2009)
During the Middle Ages, the period from roughly AD 1000-1450, the structure of castles changed greatly from wooden motte and bailey to stone keeps and defenses within stone city walls. The reason for the change was largely influenced by the crusades as Europeans went to the Holy Lands to conquer. In addition to conquering, these kings brought back a new way of designing and fortifying their castles in England, Wales and France. Without the influence of the crusades, what we think of as true middle age castles would not exist. For my paper I will analyze the impact the crusades had on forming the middle age castles by evidence surviving in the archaeological record from before and after the crusades as well as modifications done on castles to accommodate crusader changes to show the drastic influence of crusader castle fortifications upon English, Welsh and French castles.
Keywords: Crusades; Middle Ages; Castles -- Europe -- History -- To 1500